Конституційні основи правового статусу суддів у радянській Україні за Конституцією 1978 року: історико-правові аспекти - Кравчук, В. Kravchuk, V.; Кравчук, М. Kravchuk, M. (Східноєвропейський національний університет імені Лесі Українки, 2017)
Стаття присвячена аналізу конституційно-правових основ статусу суддів у радянській Україні за Конституцією 1978 року, визначено фактори, що впливали на їх формування. Досліджено динаміку окремих елементів правового статусу суддів в ході реалізації конституційних положень. Зроблено висновок про те, що хоча режим протягом аналізованого етапу не змінювався, конституційні положення, що закріплювали правовий статус судді та його окремі елементи, еволюціонували від конституції до конституції. In the process of a law-governed state formation, in the conditions of modern Ukrainian society transformation the interdependence of the justice efficiency level and the legal regulations of judge’s status is quite obvious. The successful solution of this problem depends largely on the scientific analysis and study of the local judges activities at different stages of the historical development of the judicial system, which contributes to deeper understanding of the concept specifics of the legal status of judges and its constitutional foundations. The study considers the dynamics of certain elements of the legal status of judges development during the implementation of the constitutional provisions. According to the authors, the current formation stage of the constitutional foundations of the legal status of judges is definitely characterized by internal evolution. Although the regime within the time framework under analysis did not change, the constitutional provisions that consolidated the legal status of the judge and its certain elements had been evolving from the constitution to the constitution.
Constitutional Principles of Judge’s Legal Status in Soviet Ukraine under the Constitution of 1978: Historical and Legal Aspects
Keywords: правовий статус; правовий статус судді; правосуддя; суддя; судова система; legal status; judicial status of a judge; justice; judge; judicial system